From the Poznan School of Applied Linguistics to the Cracow School of Comparative Glottodidactics. The past, the present and the future of Polish Glottodidactics - Miodunka, Władysław T.; Gębal, Przemysław E. (Glottodidactica, 2016)
To present the emergence and transformation of Polish glottodidactics, the authors refer to the earlier works of Miodunka and Gębal. The former divides the post-war history of teaching PAFL into three periods: 1) the period of applying linguistics to teaching PAFL (1950–1992), 2) the period of the development of Polish glottodidactics (1993–2003), and 3) the period of Polish glottodidactics based on European standards (2004– ). The paper ends with reflections on the emergence and evolution of comparative glottodidactics.